I Implementasi Kegiatan Market Day dalam Pembentukan Karakter Percaya Diri Anak Usia Dini Di KB/TK Ar Rohmah Surabaya - Tungga Purnama Sari Tungga (Universitas Islam Lamongan, 2025)
Market Day activities, serving as a form of experiential learning strategy, represent an effective, interactive, and engaging educational medium for developing positive character traits in early childhood. Among these traits, self-confidence is a critical aspect of social-emotional development that requires stimulation from an early age, as it directly influences a child's ability to communicate, engage in social interaction, and make decisions. This study aims to describe and analyze the implementation of Market Day activities in fostering self-confidence among students at KB/TK Ar Rohmah Surabaya. A qualitative descriptive approach with a case study design was employed. The research subjects included 30 students aged 5-6 years, 5 teachers, and 5 parents. Data were collected through observation, interviews, and documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The results indicate that Market Day activities significantly enhance children’s confidence in communication, self-expression, simple decision-making, and positive social interaction. Participation in these activities allows children to refine their communication and interaction skills while strengthening social competence and independence. Children who were previously shy and passive exhibited behavioral shifts, becoming more confident in public speaking, promoting their products, and conducting simple transactions independently. These findings confirm that a systematically designed and regularly implemented Market Day program, involving teachers and parents, serves as an effective contextual learning strategy based on real-world experience to build and reinforce self-confidence in young children.